La noopolítica como mediación en el análisis de las competencias ciudadanas (2017)
This article presents the results of a research based on the category of noopolitics, to analyze the processes of citizenship of students of the Fundación Universitaria Los Libertadores, produced in the context of discursive practices, appropriations and uses of the social network Facebook in The understanding of new subjectivities considered from this category, understood as the domination and exercise of power over the consciousness of the subjects themselves, through the consumption of information made possible by the mass media. The first part of this text approaches debates about the concepts of citizenship, social networks and noo-politics. In the second part, we present methodological considerations focused on virtual ethnography. In the end, the results and the discussion on these processes of citizenship are offered.